High‐speed heteroepitaxial growth of 3C‐SiC (111) thick films on Si (110) by laser chemical vapor deposition. Issue 3 (23rd October 2017) - Sun, Qingyun; Zhu, Peipei; Xu, Qingfang; Tu, Rong; Zhang, Song; Shi, Ji; Li, Haiwen; Zhang, Lianmeng; Goto, Takashi; Yan, Jiasheng; Li, Shusen
Abstract: 3C‐SiC (111) thick films were grown on Si (110) substrate via laser chemical vapor deposition (laser CVD) using hexamethyldisilane (HMDS) as precursor and argon (Ar) as dilution gas. The 3C‐SiC (111) polycrystalline films were prepared at deposition temperature ( T dep ) of 1423‐1523 K, whereas the 3C‐SiC (111) epitaxial films were obtained at 1573‐1648 K with the thickness of 5.40 to 9.32 μm. The in‐plane relationship was 3C‐SiC [‐1‐12]//Si [001] and 3C‐SiC [‐110]//Si [‐110]. The deposition rates ( R dep ) were 16.2‐28.0 μm/h, which are 2 to 100 times higher than that of 3C‐SiC (111) epi‐grown on Si (111) by conventional CVD. The growth mechanism of 3C‐SiC (111) epitaxial films has also been proposed.